Anoxic Brain Injury Detection with the Normalized Diffusion to ASL Perfusion Ratio: Implications for Blood-Brain Barrier Injury and Permeability - Li, N.; Wingfield, M.A.; Nickerson, J.P.; Pettersson, D.R.; Pollock, J.M. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Anoxic brain injury is a result of prolonged hypoxia. We sought to describe the nonquantitative arterial spin-labeling perfusion imaging patterns of anoxic brain injury, characterize the relationship of arterial spin-labeling and DWI, and evaluate the normalized diffusion-to-perfusion ratio to differentiate patients with anoxic brain injury from healthy controls.MATERIALS AND METHODS: We identified all patients diagnosed with anoxic brain injuries from 2002 to 2019. Twelve ROIs were drawn on arterial spin-labeling with coordinate-matched ROIs identified on DWI. Linear regression analysis was performed to examine the relationship between arterial spin-labeling perfusion and diffusion signal. Normalized diffusion-to-perfusion maps were generated using a custom-built algorithm.RESULTS: Thirty-five patients with anoxic brain injuries and 34 healthy controls were identified. Linear regression analysis demonstrated a significant positive correlation between arterial spin-labeling and DWI signal. By means of a combinatory cutoff of slope of >0 and R2 of > 0.78, linear regression using arterial spin-labeling and DWI showed a sensitivity of 0.86 (95% CI, 0.71–0.94) and specificity of 0.82 (95% CI, 0.66–0.92) for anoxic brain injuries. A normalized diffusion-to-perfusion color map demonstrated heterogeneous ratios throughout the brain in healthy controls and homogeneous ratios in patients with anoxic brain injuries.CONCLUSIONS: In anoxic brain injuries, a homogeneously positive correlation between qualitative perfusion and DWI signal was identified so that areas of increased diffusion signal showed increased ASL signal. By exploiting this relationship, the normalized diffusion-to-perfusion ratio color map may be a valuable imaging biomarker for diagnosing anoxic brain injury and potentially assessing BBB integrity.ASLarterial spin-labelingNDPnormalized diffusion-to-perfusionBBBblood brain barrierCBFcerebral blood flow